Detection of Vibration Signal by Plane Scanning Utilizing Wavefront Sensors - Yun Pan; Quan Luo; Yiyou Fan; Haoming Chen; Hongsheng Luo; Jinshan Su (Photonics)
Laser remote sensing of seismic waves is extensively utilized in earthquake monitoring and resource exploitation. This article leverages wavefront sensors’ high resolution and array detection capabilities to effectively conduct planar scanning of target areas in seismic wave laser remote sensing research, thereby properly acquiring regional vibration data. The error margin is between <semantics>1%</semantics> and <semantics>2%</semantics> relative to the source information.